Immunosuppression in Small Bowel and Multivisceral Transplantation – Literature Review - Trevizol, Alisson Paulino (2011)
Introduction: Advances in immunosuppression protocols, early diagnosis and appropriate management of Acute Cellular Rejection made Small-Bowel, Multivisceral and Modified Multivisceral Transplantation feasible. Purpose: Analyze major transplantation centers immu- nosuppression protocols. Methods: Literature review based on PubMed indexed articles, published between 2006 to 2012, focusing on adult recipients. A total of 211 adults were transplanted in seven transplantation centers. Three immunosuppression protocols were used: Protocol 1: Induction with Daclizumab and maintenance with Tacrolimus and corticosteroids. Protocol 2: Induction with Alemtuzumab and main- tenance with Tacrolimus. Protocol 3: Induction with Thymoglobulin and Rituximab and maintenance with Tacrolimus. Results: Protocol 2 had the lowest rate of acute rejection (34%), while Protocols 1 and 3 had 54% and 48% respectively. The survival rate 1 year was 70%, 79% and 81% in Protocols 1,2 and 3, respectively. Conclusion: Protocol 2 used a more potent immunosuppressant capable of reducing the level of acute cellular rejection. However, it had a lower one-year patient survival rate, possibly due to severe sepsis agravated by the strong immunosuppression. Protocol 3 seems to be the best protocol, capable of elevating patient survival rate.